2010
DOI: 10.3109/01674821003681464
|View full text |Cite
|
Sign up to set email alerts
|

Mother's anxiety and depression and associated risk factors during early pregnancy: effects on fetal growth and activity at 20–22 weeks of gestation

Abstract: To examine effects of mother's anxiety and depression and associated risk factors during early pregnancy on fetal growth and activity. Repeated measures of mother's anxiety (State-Anxiety Inventory (STAI-S)) and depression (Edinburgh Postnatal Depression Scale (EPDS)) and related socio demographics and substance consumption were obtained at the 1st and 2nd pregnancy trimesters, and fetus' (N = 147) biometric data and behavior was recorded during ultrasound examination at 20-22 weeks of gestation. Higher anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 93 publications
2
23
0
1
Order By: Relevance
“…As antenatal anxiety and depression have been demonstrated independent predictors of postnatal depression [41] and have been associated with lower fetal growth and higher fetal activity [42,43], it seems extremely important and costeffective to screen women during prenatal diagnosis. In our sample, a subset of women reported high decisional conflict during decision-making: thus performing a careful assessment aimed at identifying vulnerable women who may benefit from decision aid frameworks and genetic or group counselling [44][45][46][47] could be advisable.…”
Section: Discussionmentioning
confidence: 99%
“…As antenatal anxiety and depression have been demonstrated independent predictors of postnatal depression [41] and have been associated with lower fetal growth and higher fetal activity [42,43], it seems extremely important and costeffective to screen women during prenatal diagnosis. In our sample, a subset of women reported high decisional conflict during decision-making: thus performing a careful assessment aimed at identifying vulnerable women who may benefit from decision aid frameworks and genetic or group counselling [44][45][46][47] could be advisable.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, antenatal anxiety and depression are associated with preterm birth (Orr et al, 2007;Fransson et al, 2011) and have adverse implications for fetal neurodevelopment (Kinsella and Monk, 2009) and child outcomes (Conde et al, 2010;Alder et al, 2007). Beyond that, studies have shown that antenatal anxiety and depression are risk factors for postnatal depression (Milgrom et al, 2008); Yonkers et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, methods such as exercise that can improve short and long-term mood status are critical to overall health as psychological health and physical health are closely associated [20]. Anxiety and stress can have negative implications for maternal and neonatal health outcomes [21], so any efforts made to reduce stress and anxiety may also elicit improvements in maternal and neonatal health [22]. A previous study by Gaston and Prapavessis (2013) examining depressive mood scores in pregnant women in response to an exercise program reported a reduction in depressive symptoms after a four-week intervention [23].…”
Section: Mean ± Sd Vo 2max (Ml/kg/min)mentioning
confidence: 99%